STRATEGI KEPALA MADRASAH DALAM PEMBERDAYAAN KOMITE MADRASAH UNTUK MENINGKATKAN MUTU MAN 2 MODEL MEDAN - Riduan Pohan; Yusuf Hadijay; Muhammad Rifa’i; Muhamamd Rizki Syahputra (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study aims to determine: 1) The Principal's Strategy in Empowering Madrasah Committees to Improve the Quality of Madrasahs at MAN 2 Medan Model, 2) To determine the role and cooperation of the Madrasah Principal with the Committee in Improving Education Quality at MAN 2 Medan Model, 3) To find out Supporting and inhibiting factors in Improving the Quality of Education in MAN 2 Model Medan. This study uses a descriptive qualitative approach because in this study more emphasis on meaning, description, circumstances, and processes rather than the results of an activity. So that the data obtained by the author can be described rationally and objectively following the reality in the field. This research was conducted at Madrasah Aliyah Negeri 2 Model Medan. As for obtaining data in this study with data collection techniques as follows: 1) Observation, 2) Interview, and 3) Document Study. The results of the study indicate that the Madrasah principal's strategy is an important factor in determining the success of quality improvement in Madrasahs. The quality of education as a pillar of human resource development is very important for the progress of the nation. Even the future of the nation is often said to lie in quality education, meanwhile, quality education is only found in quality educational institutions. Therefore, efforts to improve the quality of education and the quality of learning are strategies for the creation of quality education. Based on the research results, good collaboration between the madrasah and the madrasa committee has yielded good results, there has been an increase in the quality of students and continues to fulfill learning facilities, all of which cannot be separated from the role of the madrasa committee, as the supervisor of the madrasa committee has a major role in improving the quality of madrasas. The existence of the madrasa committee is one of the success factors for madrasas in improving the quality of madrasas and as supervisors for madrasa programs that have been approved by the madrasa committee. We also need to know that every program running in the context of madrasa development does not run smoothly, of course, there are criticisms and rejections from various circles and parents of students. This is one of our efforts at this madrasa to provide an understanding of the programs that will be implemented transparently, we do this pattern so that there are no misunderstandings so we involve the madrasa committee in developing madrasas, one of which is also a supervisor.